Liquidity - A Changing Concept, Within The Post Crisis Environment - Dan Costin NIŢESCU; Florin Alexandru DUNA (Revista de Management Comparat International)
The paper aims to reflect the deep correlations between liquidity and lending mechanisms, within the banking system, both at macro and micro/individual bank’s level, related to the post crisis economical context. Liquidity represents a very important indicator within the management of the banks, not easy to understand, monitor and use. The paper provides a unique mix of financial analysis on the top five Romanian bank’s indicators, integrated within a strategic analysis of the context, regulatory framework and evolutions impacting on liquidity and lending mechanisms. The introduction includes our motivation for drafting this research paper. The second part of the paper presents the rich and latest body of literature, focusing on the evolving role of the liquidity concept and the changing relationship with other relevant indicators, within the post crisis environment. The third part presents the methodology, database, the financial analysis for relevant indicators of the top 5 Romanian banks, but also the correlations and results of our research. The forth part reflects discussions and conceptual approaches on liquidity, in order to integrate our analysis within the context, due to deep and strategic changes. The last part represents our concluding remarks.